Al- Mas'udi's methodology in his study of religions other than Islam - Alias, Majdan (Kulliyyah of Science, IIUM, 2011)
The study looks into two aspects of al-Mas'udi’s methodology in dealing with religions other than Islam; first, al-Mas'udi’s method of verifying the “reliability” or otherwise of information he gained on the religions he studied, and second, al-Mas'udi’s method of presenting the teachings of these religions. The study focuses on five of the religions dealt with by al-Mas'udi; Judaism, Christianity, Zoroastrianism, Sabianism and Hinduism. The method applied in conducting this study is textual analysis of two of al-Mas'udi’s surviving works containing his study of religions other than Islam, the MurËj and the TanbÊh.